The Ability of Soil Bacteria from Liwa Botanical Gardens to Produce Indole Acetic Acid Hormone (AIA) - Ekowati, Cristina Nugroho; Sanjaya, Agung; Umar, Suratman; Sumardi, Sumardi (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2022)
Hormon AIA berperan besar dalam memperbesar dan memperpanjang sel, pembelahan sel, khususnya pada daerah ujung tanaman. Bakteri yang memiliki kemampuan dalam menghasilkan hormon AIA diantaranya Enterobacter sp., Azospirillum sp., Klebsiella sp., Alcaligenes faecalis, Azoarcus sp., Serratia sp., Azotobacter sp., Cyanobacteria, Erwinia herbicola, Pseudomonas sp., Rhizobium, Bradyrhizobium, Agrobacterium tumafaciens. Sintesis AIA ini memerlukan senyawa tambahan berupa triptopan. Namun beberapa bakteri mampu memproduksi AIA tanpa penambahan prekursor. Penelitian ini bertujuan untuk memperoleh isolat bakteri penghasil hormon AIA dari tanah Kebun Raya Liwa. Pada ini diawali dengan isolasi bakteri tanah asal Kebun Raya Liwa, selanjutnya dilakukan uji kemampuan produksi AIA secara kuantitatif tanpa penambahan triptopan. Pengujian produksi AIA secara kualitatif dilakukan dengan menggunakan media Nutrien Broth dengan metode spektrofotometri dengan penambahan reagen salkowsky dan dilakukan pengamatan setelah 72 jam inkubasi. Data yang didapatkan disajikan dalam bentuk tabel. Hasil penelitian didapatkan 9 isolat yang mampu menghasilkan hormon AIA dengan kadar yang berbeda. Isolat penghasil AIA tertinggi yaitu isolat DT1 dengan kadar 114 ppm yang mempunyai karakteristik berbentuk bacil berwarna putih susu dan tidak berspora. AIA hormone plays a role in enlarging and elongating cells, and cell division, especially at the tip of the plant. Bacteria that have the ability to produce IAA hormones include Enterobacter sp., Azospirillum sp., Klebsiella sp., Alcaligenes faecalis, Azoarcus sp., Serratia sp., Azotobacter sp., Cyanobacteria, Erwinia herbicola, Pseudomonas sp., Rhizobium, Bradyrhizobium, Agrobacterium tumafaciens. The synthesis of AIA requires an additional compound in the form of tryptophan. However, some bacteria can produce AIA without the addition of precursors. The goal of this study was to obtain isolates of AIA hormone-producing bacteria from the soil of the Liwa Botanical Gardens. This begins with the isolation of soil bacteria from the Liwa Botanical Gardens, then a quantitative test of AIA production capability is carried out without the addition of tryptophan. Qualitative testing of AIA production was carried out using Nutrien Broth media with spectrophotometric methods with the addition of Salkowsky reagent and observations were made after 72 hours of incubation. The data obtained are presented in tabular form. The results showed that 9 isolates were able to produce the AIA hormone at different levels. The highest AIA-producing isolate was the DT1 isolate with a concentration of 114 ppm which had the characteristics of a milky white bacillus and no spores.